Corporate Restructuring: Investigating the Relationship between Divestitures and Firm Performance - Delgosha, Layla (2012)
This study examines various firm performance determinants of divestment using proportion methods across a large sample of 111 UK firms from 2008 through to 2012, which represents a much more recent period of study than currently available. Performance determinants include financial, strategy and corporate governance indicators. The study adopts panel data IV regression techniques, instrumenting lags of accounting performance within the model, allowing the analysis of time arraying influences.